Aerospace series. Heat-resisting nickel base alloy NiCr20Co3Fe3. Rm ≥ 650 MPa. Sheets and strips, cold rolled. 0, 25 mm < a ≤ 3 mm. (25th September 2023) - British Standards Institution,
No abstract available